The Evolution of Long‐Duration Cusp Spot Emission During Lobe Reconnection With Respect to Field‐Aligned Currents. Issue 7 (21st July 2020) - Carter, Jennifer A.; Milan, Stephen E.; Fogg, Alexandra R.; Sangha, Harneet; Lester, Mark; Paxton, Larry J.; Anderson, Brian J.
Abstract: We track a remarkably bright and persistent auroral cusp spot emission in the high‐latitude Northern Hemisphere polar cap, well inside the main auroral oval, for approximately 11 hr on 16 and 17 June 2012. The auroral emissions are presented in both the Lyman‐ α and Lyman‐Birge‐Hopfield bands, as observed by the Special Sensor Ultraviolet Spectrographic Imager on board two of the Defense Meteorological Satellite Programme spacecraft, and supported by detections of precipitating particles by the same spacecraft. The auroral observations are accompanied by patterns of field aligned currents, obtained from the Active Magnetosphere and Planetary Electrodynamics Response Experiment, along with ionospheric convection patterns from the Super Dual Auroral Radar Network. These data provide unprecedented coverage of a cusp spot, unusually seen in both electron and proton aurora. The location and movement of the auroral emissions, current systems, and ionospheric convection patterns are extremely distorted under the northward to Y ‐component‐dominated interplanetary magnetic field. The cusp spot emission region is associated with the sunward flow region of the ionosphere. Ion dispersion signatures are detected on traversal of the region of brightest proton auroral emissions. Proton‐excited Lyman‐ α emissions are most evident following impulses of high solar wind density. The auroral emissions, field‐aligned current patterns, and ionospheric convection are consistent with a model of a compressed magnetosphere under strongly northward interplanetary magnetic field, following an impact of an Interplanetary Coronal Mass Ejection and associated magnetic cloud at the magnetopause, inducing high‐latitude lobe reconnection that progresses increasingly tailward during the presented interval. Key Points: Extreme IMF‐By causes distortions of polar cap aurora and field‐aligned currents The study of cusp spots provides a method to remotely investigate reconnection sites at the distant magnetopause A cusp spot is found in the sunward flow region between cells of FAC under persistent northward IMF